Synthesized polyaspartic acid derivatives as corrosion and scale inhibitors in desalination operations. Issue 1 (1st January 2017) - Migahed, M.A.; Rashwan, S.M.; Kamel, M.M.; Habib, R.E.
Abstract: The present work investigated the preparation of valine of polyaspartic acid (Val-PASP) and leucine of poly aspartic acid (Leu-PASP) by using polysuccinimide. PASP compounds were used as corrosion and scale inhibitors. The prepared derivatives in this study were characterized by using Fourier transform infrared spectroscopy and nuclear magnetic resonance 1 HNMR. The electrochemical behavior of the synthesized compounds was studied on carbon steel surface using potentiodynamic polarization and electrochemical impedance spectroscopy techniques. The morphology of the C-steel specimens was surveyed using scanning electron microscopy and energy dispersive analysis of X-rays investigations. Scale agglomeration inhibition was evaluated using different concentrations of the inhibitors using standard scale test method. The highest corrosion inhibition efficiency for Val-PASP and Leu-PASP reaches 86.94 and 88.62% respectively at 250 ppm concentration, while their scale inhibition efficiency reaches 92.3 and 94.1% respectively at 125 ppm concentration.